INCREASING PROBIOTIC ON MAINTENENCE MEDIA TO GROWTH AND SURVIVAL RATE VANNAMEI SHRIMP (Litopenaeusvannamei)) - Bin Adi, Nasrul; Mulyadi, Mulyadi; M Tang, Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in December 2018 - January 2019 for 30 days at the National Broodstock Center For Shrimp and Mollusk Karangasem Bali. The purpose of this study was to determine the effect of probiotic on the growth and survival rate of vanamei shrimp (Litopeneausvannamei). Vanamei shrimp size PL25 were used in the research. The container used fiber tub with capacity 250 liters and the volume of water used is 100 liters. The treatment is probiotic, 1 ml/L, 2 ml/L, 4 ml/Land added the control treatment 0 ml/L. This research uses a completely randomized design (CRD), 4 treatments and 3 replications. The results showed that the best treatment was P2 (2 ml/L) with the addition of probioticof 2ml/L the absolute length of 6.49 cm, the absolute growth weight of 10.29 grams, Specipic growth rate of 13.33% and survival rate of 98%. Keywords: Probiotic, Vannamei shrimp, survival rate